Outbreak of Ceftriaxone-Resistant Salmonella enterica Serovar Typhi, Bangladesh, 2024 - Yogesh Hooda; Arif Mohammad Tanmoy; Sudipta Deb Nath; Anannya Barman Jui; Al Amin; Hafizur Rahman; Neoyman Nasir Shorkar; Naito Kanon; Md Asadur Rahman; Denise O. Garrett; Mohammad Shahidul Islam; Nawshad Uddin Ahmed ASM; et al. (Emerging Infectious Diseases)
We report an outbreak of ceftriaxone-resistant Salmonella enterica serovar Typhi in Bangladesh; 47 cases were identified during April–September 2024. Isolates belonged to genotype 4.3.1.2 and harbored the blaCTX-M-15 gene on the pCROB1 plasmid. This genotype-plasmid lineage represents a recent introduction, calling for strengthened surveillance, antimicrobial stewardship, and vaccination strategies.